Comparative Evaluation of Combined Therapy for Post-Thrombotic Retinopathy: Impact on Hypoxia Index and Retinal Parameters (Ukrainian Journal of Ophthalmology, 2025)
Introduction. Post-thrombotic retinopathy (PTR) is one of the most common retinal vascular diseases, complicated by the development of macular edema (ME) in 60-70% of patients. The main treatment methods include anti-VEGF therapy and laser photocoagulation; however, their efficacy is limited, and anatomical improvement does not always correspond to the restoration of retinal functional status. Therefore, there is a need to develop methods that allow for the objective assessment of hypoxic changes during therapy.Purpose. To compare the effectiveness of combined anti-VEGF therapy and subthreshold micropulse laser treatment using a yellow laser (577 nm) versus anti-VEGF monotherapy in patients with post-thrombotic retinopathy, focusing on changes in the hypoxia index (Cg) as a functional biomarker, along with anatomical and visual outcomes.Methods. The study included 60 patients (66 eyes) with PTR, divided into two groups: combined therapy (anti-VEGF + micropulse laser, 31 eyes) and anti-VEGF monotherapy (35 eyes). All patients underwent ophthalmological examination, optical coherence tomography (OCT), and electroretinography (ERG) with calculation of the Cg. Assessments were conducted at baseline and at 3, 6, and 12 months.Results. By the twelfth month, central retinal thickness in the combined therapy group had decreased to 310±25 µm compared to 360±29 µm in the monotherapy group (p=0.006). Best-corrected visual acuity improved to 0.5±0.03 versus 0.33±0.03, respectively (p=0.003). The hypoxia index (Cg) significantly decreased from 5.6±0.32 to 5.27±0.25 in the combined therapy group, while no significant changes were observed in the monotherapy group (p=0.003).Conclusion. Combined therapy using an anti-VEGF agent and subthreshold micropulse laser treatment promotes more pronounced anatomical and functional recovery of the retina in PTR. The use of the hypoxia index (Cg) provides an objective evaluation of therapy efficacy at the metabolic level and may be recommended for clinical practice.
Keywords: retinal vein occlusion; post-thrombotic retinopathy; macular edema; anti-VEGF therapy; micropulse laser; hypoxia index